1975
DOI: 10.1021/jm00246a002
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of [des-Asp1]angiotensin I as a precursor for [des-Asp1]angiotensin II (angiotensin III)

Abstract: The nonapeptide [des-Asp1]angiotensin I (IV), synthesized by Merrifield's solid-phase procedure, was tested as a possible substrate for the converting enzymes from porcine lung and plasma. IV, [des-Asp1]angiotensin II (III), [des-(Asp1,Arg2)]angiotensin II (V), [des-(Asp1,Arg2,Val3)]angiotensin II (VI), [Sar1,Ile8]angiotensin II (VII), and [des-Asp1,Ile8]angiotensin II (VIII) possessed 0.5, 20, 2, 0 less than 0.1, and less than 0.01% of the inotropic activity (rabbit atria), 1, 15, 5, 0, 3, and 0% secretory ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
1
1

Year Published

1977
1977
2002
2002

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 0 publications
0
9
1
1
Order By: Relevance
“…However, re cent studies have revealed that tissue levels of ANG III may be higher than ANG II, and much higher than those in plasma [Naruse et al, 1985]. In addition, the existence of an intracellular RAS has been demonstrated [Okamura, 1981] and it has been shown that ANG III can be produced from ANG I with out ANG II as an intermediate [Tsai et al, 1975], Given these facts, it is possible that local ANG III concentrations could become sufficient to contribute to the overall tone of certain vascular smooth muscles. Harding et al [ 1987] have recently shown that ANG III produces electrophysiological events in rat hypothalamus which are not produced by ANG II, suggesting a possible central role for the heptapeptide.…”
Section: Discussionmentioning
confidence: 99%
“…However, re cent studies have revealed that tissue levels of ANG III may be higher than ANG II, and much higher than those in plasma [Naruse et al, 1985]. In addition, the existence of an intracellular RAS has been demonstrated [Okamura, 1981] and it has been shown that ANG III can be produced from ANG I with out ANG II as an intermediate [Tsai et al, 1975], Given these facts, it is possible that local ANG III concentrations could become sufficient to contribute to the overall tone of certain vascular smooth muscles. Harding et al [ 1987] have recently shown that ANG III produces electrophysiological events in rat hypothalamus which are not produced by ANG II, suggesting a possible central role for the heptapeptide.…”
Section: Discussionmentioning
confidence: 99%
“…The Des-Asp'-angiotensin II in cerebrospinal fluid may be a metabolite excreted from brain tissue by a conventional angiotensin II-forming system, but the finding of biological activity for Des-Asp'-angiotensin II on the subfornical organ (Schlegel & Felix, 1976) raises the interesting possibility that Des-Asp'-angiotensin II may be the biologically active end product of an alternative biosynthetic pathway (Tsai, Peach, Khosla & Bumpus, 1975) in brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…17 Ang III is a naturally-occurring heptapeptide, 28 which is formed as a result of N-terminal degradation of Ang II by 29 An alternate pathway consists of conversion of angiotensin I to des-Asp 1 -angiotensin I by aminopeptidase A, 30 followed by subsequent conversion of des-Asp 1 -angiotensin I to Ang III by converting enzyme. 31,32 In the present study we have shown that Ang II, as well as Ang III, stimulates collagen gel contraction by adult rat cardiac fibroblasts; the effect of Ang II is blocked by telmisartan but not by desAsp -angiotensin II and by telmisartan. The stimulation of collagen gel contraction by rat cardiac fibroblasts by Ang II as well as by Ang III is blocked by the AT 1 -receptor antagonist, telmisartan.…”
mentioning
confidence: 47%